Expert System for Diagnosis of Diseases and Pests in Banana Plants Using Web-Based Certainty Factor Methods - Firdaus (Jurnal Mantik, 2021)
At this time, banana farmers have experienced a lot of decline due to banana diseases that have been identified too late. This is due to the banana farmers' lack of knowledge regarding the symptoms that appear in banana plants, making it difficult for farmers to distinguish between diseases that infest their crops. As one solution to the existing problems, efforts have been made to build an expert system that can identify banana plant diseases. In this study, the proposed expert system uses the method of certainty factors as a measure of the certainty of the disease being suffered in banana plants. In the application of simulation tests 30 diseases out of 85 symptoms found results with an accuracy rate of about 76.6%.